2004
DOI: 10.1159/000076697
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical T-Axis and the Spatial QRS-T Angle Are Independent Predictors of Long-Term Mortality in Patients Admitted with Acute Ischemic Chest Pain

Abstract: Objective: To investigate whether the orientation of the electrical T-axis and the spatial QRS-T angle provide independent diagnostic and prognostic information in patients presenting with acute chest pain. Methods: Patients with symptoms suggestive of acute cardiac pathology, who were seen by a general practitioner and for whom a prehospital electrocardiogram (ECG) was recorded by the ambulance service between 1992 and 1994 were investigated. The ECGs (n = 2,261) for our study population were stored for off-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 29 publications
(39 reference statements)
0
31
0
3
Order By: Relevance
“…An abnormal spatial QRS-T angle is a strong and independent predictor of cardiovascular mortality in general populations and in patients with acute ischemic chest pain. [7][8][9][10] Similarly, it has been shown to predict arrhythmic death in patients who have had myocardial infarctions and to predict cardiovascular events in women with suspected myocardial ischemia. 11,12 The calculation of the spatial QRS-T angle requires dedicated software that is not widely available and cannot be derived by visual ECG analysis after acquisition.…”
Section: Clinical Perspective P 3186mentioning
confidence: 99%
“…An abnormal spatial QRS-T angle is a strong and independent predictor of cardiovascular mortality in general populations and in patients with acute ischemic chest pain. [7][8][9][10] Similarly, it has been shown to predict arrhythmic death in patients who have had myocardial infarctions and to predict cardiovascular events in women with suspected myocardial ischemia. 11,12 The calculation of the spatial QRS-T angle requires dedicated software that is not widely available and cannot be derived by visual ECG analysis after acquisition.…”
Section: Clinical Perspective P 3186mentioning
confidence: 99%
“…Large differences between the orientations of the two wave fronts are associated with decreased survival and higher incidence of arrhythmic events in post-MI patients [22]. Also other studies have shown the prognostic value of QRSSTT angle or the T-wave axis [23][24][25]. Our QRSSTT integral parameter and mirror image in BSPM consider the amplitudes of the wave fronts, which the TCRT ignores.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, there was a significant correlation between TCRT and the VG-index in all patients, but no relationship between TCRT and negative T in any of the patients. Kors et al, 1 Kardys et al, 7 and de Torbal et al, 8 demonstrated the usefulness of the orientation of the T-axis for cardiac risk stratification, which is based on diagnostic vectorcardiography. Such an abnormal T-axis reflects repolarization abnormalities and its deviation can be attributed to ischemic changes such as T-wave inversion and ST-T changes.…”
Section: Discussionmentioning
confidence: 99%